DIALOGICAL REVELATION? ON THE RECEPTION OF DEI VERBUM 12 IN VERBUM DOMINI - Bieringer, Reimund (Asian Horizons, 2013)
The Dogmatic Constitution Dei Verbum is generally seen as a climax1 in the church’s magisterium on the significance of the Word of God in the life of the church. Dei Verbum 1 describes its own relationship to the previous statements of the church as follows: “… following in the footsteps of the Council of Trent and of the First Vatican Council, this present council wishes to set forth authentic doctrine on divine revelation and how it is handed on.” In the almost 50 years since the Council there have been relatively few official documents on revelation, Scripture and Tradition. In fact the only texts of the Magisterium to be listed here are the document of the Pontifical Biblical Commission “The Interpretation of the Bible in the Church” of 19932 and the apostolic exhortation Verbum Domini of 2010.3 By comparison we see that in the area of Catholic social teachings since Gaudium et Spes no less than seven encyclicals appeared in the same time period. In this study, we will compare the understanding of revelation, Sacred Scripture and the interpretation of Scripture in Dei Verbum with “The Interpretation of the Bible in the Church” and especially with Verbum Domini. In doing so our goal is to study aspects of the effective history and the reception of Dei Verbum. Our focus will be on the question how the understanding of revelation as dialogue evolved.